Max-min hybrid precoder design for mmWave multi-group multicasting systems - Gui, Peng; Zhao, Ming-Min; Shi, Qingjiang; Wu, Qihui (2017 IEEE/CIC International Conference on Communications in China (ICCC), 2017)
This paper investigates hybrid precoding for millimeter-wave (mmWave) multi-group multicasting systems with the consideration of max-min fairness. We formulate it as the optimization problem of maximizing the minimum signal-to-interference-plus-noise ratio among all users subject to a total transmit power constraint and constant modulus constraints. The problem is nonconvex and hard to solve due mainly to the nonlinear coupling of the digital precoder and the analog precoders. By resorting to the recently proposed penalty dual decomposition (PDD) method, the max-min hybrid precoding problem reduces to repeatedly solving four subproblems, each of which admits simple solution. Numerical results validate the effectiveness of the proposed max-min fairness hybrid precoding algorithm.